Clays as Additives in Ruminant Feed: A Quantitative Meta-Analysis of Their Effects on Enteric Methane, Digestion, Health and Productivity - Zubaer Hosen; Md. Rashidul Islam; Ravi Naidu; Bhabananda Biswas (Animals, 2026)
Clays are increasingly incorporated as feed additives for ruminants, partly inspired by animals’ natural geophagic behaviour. However, their effects on rumen function and productivity remain inconsistent in the literature. This meta-analysis synthesised 39 controlled studies (73 treatment means) to quantitatively evaluate the effects of clay supplementation on fermentation, digestibility, metabolic health, and productivity. Clay supplementation improved rumen fermentation efficiency, as indicated by reductions in methane emissions (−20.45%; p < 0.001) and ammonia-N (−11.51%; p = 0.033), along with an increase in propionate production (+4.35%; p = 0.046). These findings are consistent with proposed mechanisms not directly evaluated in this meta-analysis. Total volatile fatty acid concentration (+3.25%; p = 0.20) and rumen pH (+0.25%; p = 0.75) were not significantly altered by clay supplementation. Digestibility responses were moderately improved, particularly for neutral detergent fibre (+7.32%; p = 0.011) and organic matter (+3.06%; p < 0.001). These improvements may reflect enhanced microbial colonisation and substrate utilisation. Blood urea nitrogen decreased (−5.64%; p = 0.002) with minimal systemic effects, consistent with a primarily rumen-localised mode of action. These responses were associated with increases in weight gain (+7.96%; p = 0.002) and milk fat yield (+9.19%; p = 0.030). Meta-regression identified inclusion level and clay type as significant sources of variability (p < 0.05 for multiple outcomes). The findings indicate that clay supplementation supports methane abatement while improving rumen fermentation, digestibility, health, and productivity in ruminants.